Drivers of Merger Waves: A Revisit - Soegiharto Soegiharto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This study reexamines whether the occurrence of merger waves can be explained by the neoclassical hypothesis or the behavioral hypothesis. Using merger data for the period spanning 1990 through 2001, this study directly compares the two theories and finds that, in general, merger waves occur at the time the capital liquidity is high, firms’ stocks are overvalued, and deregulatory events exist. These suggest that the existence of an economic motivation for transactions and the availability of lower transaction cost and/or overvalued stock to generate large volume of transactions may cause industry merger waves to cluster in time